2017
DOI: 10.5194/isprs-annals-iv-4-w5-99-2017
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Semantic Comparison of Large 3d City Models in Citygml Using a Graph Database

Abstract: ABSTRACT:A city may have multiple CityGML documents recorded at different times or surveyed by different users. To analyse the city's evolution over a given period of time, as well as to update or edit the city model without negating modifications made by other users, it is of utmost importance to first compare, detect and locate spatio-semantic changes between CityGML datasets. This is however difficult due to the fact that CityGML elements belong to a complex hierarchical structure containing multi-level dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…A graph database was selected as they have been found to be efficient for storing and querying topologically connected data [24,25]. Furthermore, it has been proposed that graph theory and graph models are suitable for understanding urban topologies [26] and integrating models of urban data [27], and that graph databases can be used for the detection of spatial-semantic changes in CityGML documents [28]. The sub-networks derived from each data source are integrated into a single network by executing Neo4j Cypher queries that run 'merge' clauses on building nodes with matching identifiers across the CityGML and IFC files, and JSON stream.…”
Section: Methods Design and Implementationmentioning
confidence: 99%
“…A graph database was selected as they have been found to be efficient for storing and querying topologically connected data [24,25]. Furthermore, it has been proposed that graph theory and graph models are suitable for understanding urban topologies [26] and integrating models of urban data [27], and that graph databases can be used for the detection of spatial-semantic changes in CityGML documents [28]. The sub-networks derived from each data source are integrated into a single network by executing Neo4j Cypher queries that run 'merge' clauses on building nodes with matching identifiers across the CityGML and IFC files, and JSON stream.…”
Section: Methods Design and Implementationmentioning
confidence: 99%
“…As many IoT architectures would have a need to store many relationships between the nodes, the second objective of the study was focused on testing the applicability of the graph databases in an IoT Architecture. Previous studies indicating the potential and uses of Graph Databases for GeoInformation storage and retrieval include Agoub et al (2016) and Nguyen et al(2017).As the data in a graph database is more connected than standard SQL database, the query response times of graph databases are much faster, especially when there is a lot of relationships between objects. In parallel with these aim and objectives of the research, the user requirements are identified and unified in a generic high-level single use-case scenario.…”
Section: Overview Of the Information Integration Architecturementioning
confidence: 99%
“…For instance, in [35] the authors solely target the issue of finding the hyponyms in a specific ontology, which limits the approach to a specific ontology containing specific relation types. The issue of importing ontologies is raised in several works (e.g., [29,31,37]), whereas in [38], the authors propose to use a graph database as a "hub" to aggregate the data for further analysis.…”
Section: Related Literaturementioning
confidence: 99%
“…Some specific application areas (e.g., utilization of graph database as advisor for academic collaboration [34], mapping documents containing the smart city information into the graph nodes [37], or how ontologies mapping can contribute to the cross standard interoperability in automation [39]) are further considered in the literature. Though, our aim is to utilize the framework presented in this work for multiple domains.…”
Section: Related Literaturementioning
confidence: 99%